THE EFFECT OF PROMOTION AND SERVICE QUALITY ON REPURCHASE DECISION: CASE STUDY LYCO COFFE AND PLACE CONSUMERS AT SAMPANG - Anas, Zulviar; Faisol, Faisol (Fakultas Ekonomi dan Bisnis Universitas Alma Ata, 2024)
The aim of this research is to analyze the influence of service quality on repurchase decisions (case study Lyco Coffee and Place consumers at Sampang). The number of samples in this study was 75 respondents using the incidental sampling method. This research uses a multiple linear regression analysis method. The results of this research show that there is a simultaneous influence on the variables (promotion and service quality) on repurchase decisions, it can be seen that the significant value is below 0.05 and the calculated F value is (63.522) ˃ F table (3.12). The results of this research also show that the calculated t value for the promotion variable is (3.557), service quality is (4.302) which is greater than the t table (1.993), so it is stated that there is an influence on repurchase decisions. In the determination test, there was an influence of 62.8% of the independent variables (promotion and service quality) on the dependent variable (repurchase decision). Meanwhile, 37.2% is influenced by other variables and is not included in this regression analysis, such as location, price, brand image, brand equity and others.